2019
DOI: 10.1177/1467358419848129
|View full text |Cite
|
Sign up to set email alerts
|

The demographic impact of consumer green purchase intention toward Green Hotel Selection in China

Abstract: While there have been many prior studies examining the impact of the demographic characteristics of consumers’ green purchase attitudes and behavioral intention, results have, by no means, been conclusive. Furthermore, little attention has been paid to the green hotel industry in such studies. The purpose of this study is, therefore, to examine the relationship between age, gender, education, income, green purchase attitudes, and green behavioral intention toward green hotel selection. This study proposes a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 43 publications
(133 reference statements)
9
87
0
3
Order By: Relevance
“…Second, consistent with previous studies that showed women hold stronger pro-environmental attitudes and behaviors than men (Wang et al, 2020), the present study revealed that the younger and (Dean, Lindsay, Fielding, & Smith, 2016).…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…Second, consistent with previous studies that showed women hold stronger pro-environmental attitudes and behaviors than men (Wang et al, 2020), the present study revealed that the younger and (Dean, Lindsay, Fielding, & Smith, 2016).…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…In other words, respondents who have a college degree differ significantly from those who have a university degree in terms of buying a foreign brand (MD = -0.729, p = 0.003). Also, this result is in line with other research studies which showed that there is a statistically significant relationship between education as control variable and consumers' purchase intention (Paul & Rana, 2012;Wang et al, 2020). In this case, where the age of the respondents was used as a control variable and its influence on the purchase of a foreign brand was determined, the results of the Leven test showed that there was no homogeneity of variance in the results in each of the five groups of respondents by age (F = 2.560, p = 0.041), and that the basic assumption for the analysis of variance was not fulfilled.…”
Section: Research Results and Discussionsupporting
confidence: 92%
“…As a result, the second round of the online survey was conducted to gather more respondents for a more comprehensive representation of the target population (Saunders et al, 2011). Past studies identified demographic attributes as one of the most widely used methods to examine consumers' general or green purchase behaviour as such information is readily available and easy to apply for segmentation issues (Wang et al, 2019a). With that, the influence of demographic attributes as determinants of consumers' green purchase behaviour should be explored in future research.…”
Section: Limitationsmentioning
confidence: 99%
“…Despite the significant expansion of environmentally friendly hotels in China (more than 700 environmentally friendly hotels), various industry research reports and empirical studies revealed low levels of concern and understanding on environmentally friendly hotels among Chinese consumers (Jiang and Gao, 2019). Moreover, green purchase behaviour was extensively explored from the Western perspectives (Wang et al, 2019a). There are limited findings on the environmentally friendly hotel selection in China, resulting in the lack of a standardised definition and coherent foundation (Wang et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%